BIODIVERSITY ASSESSMENT OF MICROORGANISMS ASSOCIATED WITH TWO MARINE SPONGES (Haliclona oculata AND Amphius huxleyi) COLLECTED AT THE LANG CO BAY OF VIETNAM - Dat, Ton That Huu; Cuong, Pham Viet; Dung, Tran Thi Dung; Huyen, Vu Thi Thu; Cuc, Nguyen Thi Kim (Vietnam Journal of Marine Science and Technology, 2018)
Sponges (Phylum Porifera) are ancient sedentary and filter-feeding animals which harbour very diverse and abundant associated microbial community in their tissues with density up to 40–50% of sponge tissue volume. In this study, the diversity of associated microorganisms with two marine sponges Haliclona oculata and Amphius huxleyi collected at the Lang Co bay of Vietnam was assessed by analysis of hypervariable V3 and V4 regions of the 16S rRNA gene using Illumina MiSeq system. The taxonomic diversity of sponge-associated microorganisms was classified to different taxonomic levels (kingdom, phylum, class, order, family, and genus). Based on Bayesian classification method and reference sequences derived from Greengenes database, the associated microorganisms in studied sponges were assigned to 17 phyla (H. oculata) and 13 phyla (A. huxleyi). Many microbial taxa were detected in two sponge species, however, they were distinctive by the abundance. Proteobacteria was the most dominant phylum in both sponge species, and all of 4 classes Epsilonproteobacteria, Gammaproteobacteria, Alphaproteobacteria, and Deltaproteobacteria were found in H. oculata and A. huxleyi